The Analgesic Efficacy of Ultrasound-guided Quadratus Lumborum Block Transmuscular or Posterior Approach After Hip Surgery: A Systematic Review and Meta-analysis with Trial Sequential Analysis. Issue 9 (22nd September 2022) - Gong, Feipeng; Li, Yuxu; Wen, Jiabin; Cheng, Jinhui; Min, Huan
Abstract : Background: No review or meta-analysis exists to elucidate the efficacy and safety of quadratus lumborum block (QLB) on the pain intensity, opioid requirement, and mobilization in patients undergoing hip surgery. This systematic review and meta-analysis of randomized controlled trials were designed to compare QLB with no block or placebo (without other nerve/plexus blocks) for patients undergoing hip surgery. Methods: Two individual researchers conducted the platform searches on the PubMed, Cochrane Library, and Embase databases from inception to June 12, 2021. Only English publications were included. The pain at rest score at 12 postoperative hours was designated as the primary outcome. Secondary outcomes included rest pain at rest scores at 6 and 24 postoperative hours, dynamic pain score at 6, 12, and 24 postoperative hours, total opioid consumption, postoperative nausea and vomiting, and patient satisfaction. Results: Seven trials including 514 patients were included. When compared with controls, the QLB technique significantly reduced pain at rest scores at 12 hours after surgery (mean difference −1.15, −1.52 to −0.77, P <0.0001). The secondary outcomes were limited by heterogeneity: secondary pain outcomes and opioid consumption were consistently improved with QLB ( P <0.05); patient satisfaction and postoperative nausea and vomiting were similar between the groups based on the Inverse Variance Heterogeneity model ( P >0.05). The overall quality of evidence was moderate. Conclusions: There is moderate evidence that QLB employment in hip surgery produces significant reduction in pain scores and opioid consumption within 24 hours. QLB appears to be an appropriate option for postoperative analgesia after hip surgery.